Morphometric and molecular characterization of Sarcocystis spp. in cattle (Bos spp.) and goats (Capra hircus) collected from the Shah Alam abattoir / Ng Yit Han - Ng , Yit Han (2016)
Sarcocystosis in meat-producing animals is a major cause of reduced productivity in many countries, especially those that rely on agriculture. Although several diagnostic methods are available to detect sarcocystosis, many are too time-consuming for routine use in abattoirs and meat inspection centres, where large numbers of samples need to be tested. Current establish method (transmission electron microscope) for Sarcocystis spp. identification is expensive and time-consuming. Alternatively, tissue compression technique can rapidly detect sarcocysts in tissue samples. Additionally, cysts measurement in corroboration with genotyping of 18S rDNA allows comprehensive species identification. Sequences of Sarcocystis spp. can also be analysed via phylogenetic tree to provide better understanding of the evolution of Sarcocystis spp. corresponding to the respective intermediate hosts. Furthermore, phylogeny analysis enables effective species differentiation of sarcocyst, especially for those closely related species that are morphologically similar. Tissue samples of cattle and goats were collected from the Shah Alam abattoir, Selangor. Samples were pre-screened for the presence of sarcocysts via tissue compression technique (group of unstained (methylene blue) and stained condition). Positive sample tissues were further confirmed by nested PCR by targeting the 18S rDNA regions. Statistical calculations were done to determine the efficacy of stain-based technique compared to the standard unstained technique of sarcocysts detection in tissue samples. Besides, sarcocysts detected in tissues were measured for morphometric study and then subjected for genotyping to determine the identity. Sequences were then used for phylogenetic tree analysis. A total of 583 tissue samples were collected. Of these, 245 samples were positive under pre-screening phase. Mc Nemar’s and Cohen kappa analysis show that stain-based technique is able to detect three-folds higher sarcocysts and it is statistically in concordance with nested PCR outcome (gold standard). Morphometric study deduced that possibly one Sarcocystis sp.